2020
DOI: 10.3390/app11010318
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy Improvement of Intraoral Scanning and Buccal Bite Registration Using Healing Abutment as Landmarks: An In Vitro Study

Abstract: This study aimed to determine the influence of the healing abutment (HA), placed at the implant placement site, on the accuracy of intraoral scanning and buccal bite registration in quadrant maxillary and mandibular models when using three types of intraoral scanner (IOS) and elucidate the distribution of arch distortion. Six experimental groups based on whether the HA was connected and the location of missing teeth were digitized using one laboratory scanner (Identica T500) and three IOSs (Trios 3, CS3600, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…However, when multiple teeth are missing, the accuracy of VIR may not meet clinical standard, rendering a complete digital work ow on multiple implants invalid. [1,20,21] Previous research [17] explored the use of healing abutments to improve interocclusal relationship accuracy in IOS on stone models, however no clinical study of a complete digital work ow on multiple implant-supported crowns was reported. Therefore, this study represents a signi cant contribution to the eld.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, when multiple teeth are missing, the accuracy of VIR may not meet clinical standard, rendering a complete digital work ow on multiple implants invalid. [1,20,21] Previous research [17] explored the use of healing abutments to improve interocclusal relationship accuracy in IOS on stone models, however no clinical study of a complete digital work ow on multiple implant-supported crowns was reported. Therefore, this study represents a signi cant contribution to the eld.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16] This distinct geometry facilitates the stitching process and signi cantly improves the accuracy of digital impressions. Similarly, lack of geometry on an edentulous area also compromises the accuracy of VIRs, but this problem can be overcome by using auxiliary devices [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This distinct geometry facilitates the stitching process and significantly improves the accuracy of digital impressions. Similarly, lack of geometry on an edentulous area also compromises the accuracy of VIRs, but this problem can be overcome by using auxiliary devices [17].…”
Section: Introductionmentioning
confidence: 99%
“…Jin et al [17] reported the use of healing abutments on the implants significantly improves the VIRs of partial edentulous area in laboratory setting. However, no clinical study was available to explore improving the accuracy of VIRs with the help of auxiliary devices and facilitate their use in restoring multiple implant-supported crowns using a digital workflow.…”
Section: Introductionmentioning
confidence: 99%